A central role for Plasmodium falciparum subtelomeric regions in spatial positioning and telomere length regulation - Figueiredo, Luisa M. (Oxford University Press, 2002)
In the protozoan malaria parasite, Plasmodium falciparum, the telomere-associated sequences (TASs) of the 14 linear chromosomes display a similar higher order organization and form clusters of four to seven telomeres localized at the nuclear periphery. Experimental evidence has shown that the physical tethering of chromosome ends enhances the ectopic recombination between gene families involved in antigenic variation and parasite sequestration. Using FISH analysis, we observed that chromosome ends lacking the subtelomeric region are usually delocalized from telomere clusters, but still remain at the nuclear periphery. This indicates that subtelomeric DNA is necessary for cluster formation but is not essential for peripheral positioning. Intriguingly, these truncated chromosomes have unusually long telomeric tracts (up to three times longer than average length), showing that TASs play a role in telomere length regulation. On these chromosomes, the newly formed telomere frequently extends from truncated genes leading, in some cases, to the transcription of telomeric DNA. The implications of both subtelomeric gene expression and nuclear architecture in the virulence of this serious human pathogen are discussed.